Main palm heart-producing species cultivated in Brazil - Duarte, Ana Carolina Oliveira; Amaral, Marina Milanello do (Scientia Agraria Paranaensis, 2022)
Among the most targeted species for obtaining palm hearts, Euterpe edulis, popularly known as Juçara palm hearts, stands out and is threatened with extinction. The rational use of other palm trees for the production of palm hearts has been one of the alternatives to reduce the pressure of exploitation on the juçara palm: Archontophoenix alexandrae, Bactris gasipaes, Euterpe oleracea. This narrative literature review aims to discuss the four main palm tree species in Brazil. It is noted that despite the risk of extinction, there is still illegal and clandestine extraction of the Euterpe edulis species. The species of the same genus, E. oleracea, has significant cultivation in the northern region, but mainly due to the use of the fruit. Archontophoenix alexandrae is an exotic species that has adapted well to Brazil, and I offer a quality palm heart in the Brazilian market. The most cultivated species today is peach palm, it has advantages such as high tillering and shorter cultivation time.